Elaboração, realização e resultados da aplicação de uma proposta alternativa para o ensino de ciências em aulas experimentais - Santos, Edvaldo José dos (2013)
The main objective of this dissertation, linked to Curriculum Research, Teaching and Teaching Methods of Natural Sciences and Mathematics, consisted of preparing an alternative proposal for teaching physics lab, anchored by a new methodological possibility of teaching. The adopted theoretical perspective indicated the fundamentals that discuss the need to insert innovative methods to make this education more accessible and less intimidating. The study relied on the concepts of reflective teacher and interdisciplinary nature, used as a reference for developing an activity of investigative character. In order to build critical awareness of the student, the proposal was applied to a specific group of students, checking for changes in attitudes as a result of this process of teaching and learning. After application of the material in a Federal Institute of Education, the city of Aracaju / SE, the results show that the developed proposal trends to facilitate student learning and reasoning.